Rules of Evidence in the Crime of Electronic Fraud - Issa, Prof. Dr. Hussein Abd Ali; Sharif, Shilan Muhamad (Journal of Legal and Political Studies, 2019)
This research was devoted to the study of the rules of criminal evidence in the crime of electronic fraud through a statement of the main proof of evidence adopted by the investigation and judicial bodies in this type of crimes of information , especially testimony ,evidence ,experience and recognition ,and to clarify the nature and importance of digital evidence and explain the extent of its argument in proving a crime of electronic fraud, and to arrive at the appropriate of recommendation for the development of criminal procedure legislation regarding the criminal evidence in the crime of electronic fraud in particular.
Keywords: criminal evidence; electronic fraud; digital evidence; criminal procedure; testimony